Increasing PyonPyon’s Instagram Traffic through Livestreams - Anthony Febrianto Yusran (Institute of Research and Community Outreach - Petra Christian University, 2022)
PyonPyon is a start-up company in Jakarta that runs on the healthy-beverage industry. During the author’s final assessment internship, PyonPyon was having trouble on getting traffic or even public exposure on their main social media account, Instagram. The author then identified PyonPyon’s problem as low traffic and public exposure on their main social media marketing. Therefore, a solution was implemented by putting PyonPyon on an endorsement through live streamers and posting unique Instagram post. Supporting the solution, the author needs to know the level of brand awareness and consumer’s buying behavior. Thus, a survey was created to 36 respondents from across Indonesia. From the questionnaire, result showed that PyonPyon’s brand awareness is currently at the lowest stage, which is “unaware of brand”. After the survey and implementing the solution, result showed that by putting PyonPyon on live streamers that has decent live views, it can raise the Instagram traffic of PyonPyon. The author decided that endorsement in live streams is a good way to gain traffic and to gain public exposure, also increases PyonPyon brand awareness, since the target market, or the live viewers can check out PyonPyon’s Instagram and product at the same time while it is shown on the show. The author created a strategy by applying theories such as measuring levels of brand awareness from Aaker (1991), methods to increase brand awareness from Liando and Setyawati (2014), social media marketing from Hayes (2021), and advertising from Yakup (2011).